1987
DOI: 10.1128/iai.55.10.2332-2340.1987
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effects of Centipeda periodontii: selective cytotoxicity for lymphocytes and monocytes

Abstract: We have examined soluble sonic extracts prepared from several strains of Centipeda periodontii for their ability to alter human lymphocyte function. These organisms were isolated from subgingival plaque of patients with periodontal disease. We found that sonicates from several, but not all, strains of C. periodontii caused a dose-dependent inhibition of lymphocyte responsiveness to concanavalin A, phytohemaggluttinin, pokeweed mitogen, and formalinized Staphylococcus aureus. Inhibition was associated with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Products of Corvnehacterium parvum, Actinomyces viscosus and oral spirochetes such as Treponema denticota affect macrophages, provoking the release of mediators such as hydrogen peroxide and prostaglandin that are capable of inhibiting lytnphocyte function (7,14,15). Other bacteria produce toxins which selectively kill itnmune cells (1,12). Preliminary data suggest that B. intermedius inhibit itntnunological responses during the early stages (within first 24 h) of cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Products of Corvnehacterium parvum, Actinomyces viscosus and oral spirochetes such as Treponema denticota affect macrophages, provoking the release of mediators such as hydrogen peroxide and prostaglandin that are capable of inhibiting lytnphocyte function (7,14,15). Other bacteria produce toxins which selectively kill itnmune cells (1,12). Preliminary data suggest that B. intermedius inhibit itntnunological responses during the early stages (within first 24 h) of cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Shenker et al reported that soluble sonic extracts of several C. periodontii strains possessed the activities causing immunogenic dysfunction or immunosuppression, which may make it easy for bacteria to infect and colonized gingival tissues, and may contribute to the initiation and progression of the early stages of periodontal disease. (24,25) In this study, it has been revealed that the endotoxic activities of C. periodontii LPS are comparable to those of E. coli LPS. Although the pathogenic mechanisms of periodontopathic organisms are complex and require further study, the data here suggest that C. periodontii LPS may be one possible pathogenic factor relating this bacterium to periodontal disease.…”
Section: Resultsmentioning
confidence: 61%
“…While the nature and contribution of the immune system to the pathogenesis of periodontal disease are poorly understood, recent studies suggest that the development of these disorders may be associated with immunologic dysfunction (reviewed in reference 16). Although the basis for this dysfunction is unclear, we have found that several putative periodontal pathogens are capable of inhibiting human lymphocyte responsiveness (17)(18)(19)(20)(21). The ability of microorganisms to suppress the immune response of the host may affect the course of initial infection by facilitating spread, multiplication, and persistence and may lead to enhanced susceptibility to infection by secondary pathogens (reviewed in references 15 and 28).…”
mentioning
confidence: 93%